1995
DOI: 10.1097/00008469-199502000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks among male farmers in Sweden

Abstract: 7 Gallagher RP, Bajdik CD, Fincham S et al. Chemical exposures, medical history, and risk of squamous and basal cell carcinoma of the skin. Cancer Epidemiol Biomarkers Prev 1996; 5:419-24. 8 De Hertog SAE, Wensveen CAH, Bastiaens MT et al. Relation between smoking and skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 0 publications
0
49
1
2
Order By: Relevance
“…Farmers have been found to have elevated rates of lip cancer (8)(9)(10)(11). Lip cancer among Norwegian farmers was found to be associated moderately with grain production, fungal forecasts (events of wet and temperate conditions known to favor fungal growth and mycotoxin formation) and solar exposure (12).…”
Section: Discussionmentioning
confidence: 99%
“…Farmers have been found to have elevated rates of lip cancer (8)(9)(10)(11). Lip cancer among Norwegian farmers was found to be associated moderately with grain production, fungal forecasts (events of wet and temperate conditions known to favor fungal growth and mycotoxin formation) and solar exposure (12).…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Studies in the United States, Canada and Europe have reported 6-28% reductions in overall mortality and/or cancer mortality when compared to rates in the general population. 64,[66][67][68][69][70][71][72][73][74][75] The lower overall mortality rate among farmers may be attributable to healthier lifestyle practices. As an occupational group, farmers have a lower incidence of smoking-related cancers, 64,66,67,70,72,73 reflecting lower smoking rates.…”
Section: Agriculture and Farmingmentioning
confidence: 99%
“…[76][77][78][79] In addition, agricultural work may be considered a salubrious lifestyle, encompassing physically demanding activities that require exercise, strength and stamina, as well as dietary choices rich in fresh foods. 76 Findings from studies of farming and multiple myeloma have been mixed, however, ranging from relative risk estimates below 1.0 64,65,67,[69][70][71][72][73] to increased risks in excess of 3-fold, 70,71 either overall or for specific subgroups.…”
Section: Agriculture and Farmingmentioning
confidence: 99%
“…Occupational exposure has been sought, as various rare cancers are caused by exposures occurring in the workplace (12). Occupations involving welding (13)(14)(15)(16)(17), farming (13,14,(18)(19)(20)(21)(22)(23)(24), and exposure to chemicals (13,25,26) have been the most frequently mentioned. However, no causative agent has been established, and contradictory evidence is common.…”
mentioning
confidence: 99%